Implementasi Sistem Evaluasi Kinerja Dosen untuk Mendukung Peningkatan Kualitas Pembelajaran - Sholihah Ayu Wulandari; Trismayanti Dwi Puspitasari; Aji Seto Arifianto; Nugroho Setyo Wibowo; Rifqi Aji Widarso (Jurnal Medika: Medika, 2026)
Lecturer performance evaluation is a crucial aspect in improving the quality of learning in higher education. However, current evaluation processes are often conducted generally and fail to accurately represent the performance of individual lecturers. To address this issue, a web-based lecturer performance evaluation system was developed at the Department of Information Technology, State Polytechnic of Jember. This system allows students to directly evaluate lecturers through a Likert-scale questionnaire covering three main aspects: pre-learning, learning implementation, and post-learning activities. The method used in this program includes system design, implementation, and trials involving both lecturers and students. The results show that the system facilitates a more transparent, efficient, and real-time evaluation process, generating accurate performance reports that support accreditation and internal quality assurance. Moreover, the system encourages two-way feedback between students and lecturers as a foundation for continuous improvement in the teaching process. Therefore, the implementation of this JTI Innovation is a strategic step toward building a culture of quality and transparency within higher education institutions.